PHYTOCHEMICAL AND ELEMENTAL PROFILING OF LIMONIUM OTOLEPIS GROWING IN THE FERGANA REGION, UZBEKISTAN: HPLC AND ICP-OES ANALYSIS - Urmonov, Dadahon; Ibragimov, Alidjan (Химия растительного сырья, 2025)
This study aimed to investigate the phenolic and elemental composition of the aerial parts of Limonium otolepis growing in the Fergana region, Uzbekistan. High-performance liquid chromatography (HPLC) analysis was employed to identify and quantify the phenolic compounds present in the plant. The analysis revealed four major phenolic compounds, viz. rutin, apigenin, gallic acid, and hyperoside. The concentrations of these compounds were measured, with gallic acid showing the highest concentration at 77.521 mg/100 g, followed by rutin at 38.968 mg/100 g, apigenin at 26.351 mg/100 g, and hyperoside at 18.254 mg/100 g. Additionally, elemental analysis using inductively coupled plasma-optical emission spectrometry (ICP-OES) was conducted to determine the macro- and microelemental content of the plant. Significant levels of essential elements such as potassium, calcium, magnesium, and iron were found, highlighting the plant’s nutritional and therapeutic potential. Potassium, in particular, was present at 586.241 mg/10 g, underscoring its importance for metabolic processes. The absence of harmful heavy metals such as lead and mercury further supports the safety of the plant for use in food and medicinal applications. These findings underscore the potential of L. otolepis as a valuable source of bioactive compounds and essential nutrients, making it a promising candidate for the development of phytopreparations and nutritional supplements.